If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5x + -4x + 12 = 100x Reorder the terms: 12 + 5x + -4x = 100x Combine like terms: 5x + -4x = 1x 12 + 1x = 100x Solving 12 + 1x = 100x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-100x' to each side of the equation. 12 + 1x + -100x = 100x + -100x Combine like terms: 1x + -100x = -99x 12 + -99x = 100x + -100x Combine like terms: 100x + -100x = 0 12 + -99x = 0 Add '-12' to each side of the equation. 12 + -12 + -99x = 0 + -12 Combine like terms: 12 + -12 = 0 0 + -99x = 0 + -12 -99x = 0 + -12 Combine like terms: 0 + -12 = -12 -99x = -12 Divide each side by '-99'. x = 0.1212121212 Simplifying x = 0.1212121212
| 6.5=2.4-4.9 | | 7(6+5b)=b-26 | | 6x+2-(2x)=x+5-(-5) | | 3x^2+24x-540=0 | | 7+4(2a+5)=-13 | | 5-2x+x=-1x+5x+-10 | | 4x-8y=28 | | x^5+2x^4+x^3=0 | | 5+2x+x=-x+5x-10 | | 2p+7=5-(9p+4) | | 6-4m=-8m-10 | | math=dumb | | -23+5a=14a+49 | | (2x+5)(3x^2+4x+7)= | | 5w+8-12=16+-15w | | 0=-3(3a-9) | | 5-2x+x=-x+5x-10 | | 4x+16=-20 | | 6-9x=15(x+2) | | 4x^2-41x+71=0 | | -8(7+2x)=-2+2x | | 3x-6x= | | 3.2-9x+7.1-3x= | | 10(x+7)=9(x-7)+x | | -39=-3(3a+4) | | 7-4n=-3-18-18n | | 8n=1 | | 5x-4(x-8)=100x | | 3(t-2)=2t+11 | | 9=2a+1 | | p+8-3p=14 | | -8(7+2x)=-2+2k |